Studi Komparatif Rencana Anggaran Biaya Klinik PT. Delta Subur Permai Berdasarkan SNI - Basiri, Syamsu; Ibrahim, Malik; Lutfie, Mukhtar (Universitas Negeri Gorontalo, 2025)
PT. Delta Subur Permai (DSP) is a subsidiary of Kencana Agri Group operating in Batui District, Banggai Regency, Central Sulawesi. This company is engaged in oil palm cultivation; however, since its establishment, it has lacked adequate health facilities, resulting in suboptimal employee health services. For this reason, the company took the initiative to build a clinic that supports the health needs of its workers. In the planning process, the budget plan data used by the contractor still refers to the contractor's internal calculation method. Therefore, this study focuses on analyzing the Cost Budget Plan (RAB) for clinic construction using the SNI analysis method. The objectives of this study are determine the RAB for PT DSP's clinic construction based on unit prices from the Banggai Regency Government with SNI analysis and to compare more efficient methods in preparing the RAB. The study employed a comparative quantitative method, specifically comparing variable values across different populations or samples. The results showed that the RAB value using the SNI method was Rp. Rp. 313,300,820, which is higher than the contractor's method of Rp. 297,186,771. This confirms the difference in calculation results between the two methods.